On the death of Jews : photographs and history - Fresco, Nadine (Berghahn, 2021)
"In December 1941, on a shore near the Latvian city of Liepaja, Nazi death squads and local collaborators murdered in three days more than 2,700 Jews, the majority of whom were women and children, most men having already been shot during the summer. The murderers took pictures of the December killings. These photographs are among the very rare pictures from the first period of the extermination, during which more than a million Jews from the Baltic to the Black Sea were shot to death. By showing the importance of photography in understanding persecution, Nadine Fresco offers a powerful meditation on the images while confronting the essential questions of testimony and guilt"--